2020
DOI: 10.1007/s12036-020-09668-1
|View full text |Cite
|
Sign up to set email alerts
|

UVIT/AstroSat studies of blue straggler stars and post-mass transfer systems in star clusters: detection of one more blue lurker in M67

Abstract: The blue straggler stars (BSSs) are main-sequence (MS) stars, which have evaded stellar evolution by acquiring mass while on the MS. The detection of extremely low mass (ELM) white dwarf (WD) companions to two BSSs and one yellow straggler star (YSS) from our earlier study using UVIT/AstroSat, as well as WD companions to main-sequence stars (known as blue lurkers) suggest a good fraction of post-mass transfer binaries in M67. Using deeper UVIT observations, here we report the detection of another blue lurker i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Similarly, stellar collisions and mergers are also expected to yield rapidly rotating stars (Sills et al 2001(Sills et al , 2005. Recently, Subramaniam et al (2020) found a correlation between T ๐‘’ ๐‘“ ๐‘“ of WD and ๐‘ฃ ๐‘ ๐‘–๐‘›๐‘– of BSS. The BSSs with the hottest WD are fast rotators, whereas the slowest rotation is found for the BSS with the coolest WD (WOCS 5005).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Similarly, stellar collisions and mergers are also expected to yield rapidly rotating stars (Sills et al 2001(Sills et al , 2005. Recently, Subramaniam et al (2020) found a correlation between T ๐‘’ ๐‘“ ๐‘“ of WD and ๐‘ฃ ๐‘ ๐‘–๐‘›๐‘– of BSS. The BSSs with the hottest WD are fast rotators, whereas the slowest rotation is found for the BSS with the coolest WD (WOCS 5005).…”
Section: Discussionmentioning
confidence: 98%
“…A recent MT is expected to leave behind a hot companion to the BSS (and blue lurkers), whereas mergers leave behind a single BSS. UV investigations have revealed the presence of hot WD companions to the BSSs and MS stars (Knigge et al 2008;Gosnell et al 2015;Sindhu et al 2019;Leiner et al 2019;Jadhav et al 2019;Sahu et al 2019;Sindhu et al 2020;Subramaniam et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, depending upon the environment during merger or collision, the mass and age of BSs are slightly different from single star evolution (Sills et al 2009;Sun et al 2021). Due to their extremely large effective temperature, a UV imaging study is a powerful tool to identify and trace the properties of BSs in GCs (Ferraro 2000;Raso et al 2017;Ferraro et al 2018;Sindhu et al 2019;Sahu et al 2019a;Subramaniam et al 2020;Kumar et al 2021a).…”
mentioning
confidence: 99%